2011
DOI: 10.5754/hge11278
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Surgery in Patients Over 80 Years Old

Abstract: Colorectal resections can be performed with good results in elderly patients. A colic disease must be detected before the patient develops a surgical complication because urgent surgery has more complications and deaths compared to elective surgery, especially for older patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
6
0
2
Order By: Relevance
“…Studies have shown that co-morbidities as diabetes, renal insufficiency, and age are on the one hand, amongst others, independent risk factors for CAL [20], but are also negative predictors for secondary peritonitis as well [21]. Contrastingly, other studies show no increased risk of complication in elderly [22,23]. This study shows that age and higher ASA score do influence the surgeon, leading to a tendency to preserve the anastomosis in younger patients and breakdown the anastomosis in older patients.…”
Section: Discussionmentioning
confidence: 86%
“…Studies have shown that co-morbidities as diabetes, renal insufficiency, and age are on the one hand, amongst others, independent risk factors for CAL [20], but are also negative predictors for secondary peritonitis as well [21]. Contrastingly, other studies show no increased risk of complication in elderly [22,23]. This study shows that age and higher ASA score do influence the surgeon, leading to a tendency to preserve the anastomosis in younger patients and breakdown the anastomosis in older patients.…”
Section: Discussionmentioning
confidence: 86%
“…We propose that 'reinsertion of the NG tube' should be adopted as the standardized definition in the future to allow meaningful prospective studies that evaluate the risk factors for PPOI and strategies for prevention. [65] Abdominal distension or vomiting, based on clinical judgement Kahokehr, 2010 [42] NR Singh, 2011 [69] Abdominal distension or vomiting, based on clinical judgement Abodeely, 2011 [38] NR Raue, 2011 [43] NR Pelloni, 2012 [59] NR Kim, 2013 [34] NR Kolozsvari, 2013 [52] NR Manceau, 2013 [56] NR RCTs Ortiz, 1996 [22] Two episodes of vomiting Ortiz, 1996 [31] Two episodes of vomiting Schwenk, 1998 [23] NR Stewart, 1998 [25] Vomiting of > 100 ml on two occasions within 24 h Smith, 2000 [24] Clinical judgement Targarona, 2002 [32] NR Taqi, 2007 [26] NR Hewett, 2008 [30] NR El Nakeeb, 2009 [19] Two episodes of vomiting without bowel movement Kang, 2010 [29] NR Ng, 2010 [21] NR Deng, 2013 [18] NR Zaghiyan, 2013 [28] NR NG, nasogastric; NR, not reported.…”
Section: O6mentioning
confidence: 99%
“…[9][10][11] Kolorektal cerrahide, ileri yaşın kanser cerrahisinde bir kısıtlama olmadığını, yandaş hastalıkların ve kanser evresinin tedavi sonuçlarını belirlediği belirtilmektedir. [7,11] Yine Ragg ve ark., [12] majör kolorektal kanser cerrahi geçiren 887 vaka üzerinde yaptıkları çalışmada yüksek ko-morbidite sayısının mortalite ve morbidite için risk faktörü olduğunu belirtmişlerdir. Biz de çalışmamızda ileri yaşla birlikte yandaş hastalıkların daha fazla olduğunu ve bunun da mortalite ve morbidite için risk faktörü olduğunu gözlemledik.…”
Section: Discussionunclassified
“…[2] Anastomoz kaçağı başta olmak üzere intraabdominal komplikasyonların dışında, çoğunluğu ileri yaş grubunda olan bu hastalarda yandaş hastalıkların varlığı morbidite ve mortaliteyi artırmaktadır. [1,2,7,8] Morbidite ve mortaliteyi etkileyen bu faktörlerin belirlenmesi ve önlemlerinin alınması rektum kanserinde tedavinin başarısını artıracaktır. [9][10][11][12] Biz bu çalışmada spesifik bir kolorektal cerrahi kliniği olarak çalışmayan bir genel cerrahi kliniğinde, rektum kanseri cerrahisinde düşük hasta yoğunluğuna sahip cerrahlar tarafından uygulanan operasyonlarda mortalite ve morbiditeye etki eden faktörleri araştırmayı ve literatür eşliğinde tartışmayı amaçladık.…”
Section: Introductionunclassified